Controversies in point-of-care 3D printing for oncological and reconstructive surgery with free software in oral and maxillofacial surgery: European regulations, costs, and timeframe - Gómez, V.J.; Martín-González, A.; Zafra-Vallejo, V.; Zubillaga-Rodríguez, I.; Fernández-García, A.; Sánchez-Aniceto, G. (International journal of oral and maxillofacial surgery, 2024)
The aim of this paper is to discuss the controversies surrounding the most recent European regulations, as well as the cost, for a 3D printing workflow using free-source software in the context of a tertiary level university hospital in the Spanish public health system. Computer-aided design and manufacturing (CAD/CAM) for head and neck oncological surgery with the printing of biomodels, cutting guides, and patient-specific implants has made it possible to simplify and make this type of highly complex surgery more predictable. This technology is not without drawbacks, such as increased costs and the lead times when planning with the biomedical industry. A review of the current European legislation and the literature on this subject was performed, and comparisons made with the authors’ in-house 3D printing setup using free software and different 3D printers. The cost analysis revealed that for the cheapest setup with free software, it would be possible to amortize the investment from case 2, and in all cases the initial investment would be amortized before case 9. The timeframe ranged from 2 weeks with the biomedical industry to 72 h with point-of-care 3D printing. It is now possible to develop point-of-care 3D printing in any hospital with almost any budget.